Subsidies, Information, and the Timing of Children's Health Care in Mali - Sautmann, Anja; Brown, Samuel; Dean, Mark (The Review of Economics and Statistics, 2025)
Progress on child mortality requires better curative care, but common policies to improve access risk reducing underuse incompletely or creating overuse. In an RCT of 1,768 children in Mali we analyze how subsidized care and community health worker (CHW) visits affect the targeting of acute care, using nine weeks of daily health data to measure demand conditional on need for care per WHO standards. Parents are five times more likely to seek care when medically indicated. Subsidies increase utilization by over 250%, significantly reducing underuse with moderate effects on overuse. CHW do not improve efficient health care utilization on average.